Challenges in Patients with Trisomy 21: A Review of Current Knowledge and Recommendations - Jennifer Robinson; Manca Tekavčič Pompe; Christina Gerth-Kahlert (Journal of Ophthalmology)
Purpose. To summarize and review the common ophthalmic anomalies in children with trisomy 21 (Down syndrome) in order to propose an update to current clinical recommendations. Methods. A retrospective chart review, systemic literature review, and international survey of the frequency of ocular abnormalities, screening schedules, and challenging aspects examining children with trisomy 21. The chart review included patients treated at the Department of Ophthalmology at the University Hospital of Zurich over a two-year period. The international survey was submitted to the members of the Swiss Society of Ophthalmology, Slovenian Ophthalmological Society, and European Pediatric Ophthalmology Society. Results. Analysis of 52 patient records during the study period revealed refractive errors (astigmatism: 54% of patients, hyperopia: 26%, and myopia: 15%) as the most common diagnosis, whereas childhood cataract was reported in 5%. This is in concordance with the extended literature review of 249 publications, although congenital cataracts were reported to be higher than at our institution. The survey participants reported great challenges in taking care of these patients, despite their long professional experience (73% with over 10 years of experience). Conclusion. Care and treatment of children with trisomy 21 continues to be demanding for paediatric ophthalmologists. We recommend the following examination schedule for these patients: first, ophthalmological examination at 6–12 months of age, then once in 3–6 months for children under 2 years of age, once in 6 months for children 2–5 years of age, annually for children 5–10 years of age, and thereafter, to be decided on an individual basis depending on the presenting ocular abnormalities of the patient.